TRANSPORT MANAGEMENT IN TOURISM - THE IMPORTANCE OF TRANSPORT INFRASTRUCTURE FOR THE DEVELOPMENT OF TOURIST DESTINATIONS IN SERBIA ON THE EXAMPLE OF THE CITY OF KRALJEVO AND ZLATIBOR DISTRICT - Tornjanski, Aleksandra (The Business of Tourism, 2023)
Transport infrastructure in Serbia constitutes an integral part of the material basis of tourism. The development of a tourist destination is impossible without the development of transport infrastructure. Traffic infrastructure is an integral part of a tourist destination and a condition for the development of all activities and processes in the destination. The attractive factors of the tourist destination itself cannot be successfully valorized if there is no good traffic infrastructure and traffic connections. In fact, the development of traffic contributed to the movement of people and the development of tourism, especially the construction of traffic infrastructure, railways, roads and airports, which have led to modern mass tourism. Improving the quality of traffic in terms of speed and comfort of travel is an extremely important factor in the tourist offer today. Destinations that have quality traffic infrastructure and good traffic connections are more attractive as destinations for tourists. An important prerequisite for the development of tourism in destinations is the development of traffic infrastructure, that is, the position of the destination in relation to the main traffic roads. The development of air traffic and the existence of an airport with flights to emitting markets is one of the important prerequisites for the development of tourism in Serbia. The region around the city of Kraljevo and the Zlatibor district have an extremely good position for the further development of Serbia’s tourist offer. The construction of transport infrastructure is the first and decisive factor that affects the growth and development of tourism in a certain tourist destination. Traffic infrastructure extremely strongly defines and directs the economic and tourism development of Serbia. The inclusion of the airports in Kraljevo and Užice, as well as the further inclusion of other smaller airports, especially in those locations that gravitate towards a larger number of cities, will strongly influence the improvement of tourism at the country level. Multiple benefits from the inclusion of smaller airports in Serbia will be most easily seen through the increase in the number of passengers at these airports, but the real effects will be seen when the mobility of people, primarily from the region, will be noticed in the years to come.